Psychobehavioral Responses, Post‐Traumatic Stress and Depression in Pregnancy During the Early Phase of COVID‐19 Outbreak - Zhang, Casper J. P.; Wu, Huailiang; He, Zonglin; Chan, Nga‐Kwo; Huang, Jian; Wang, Huiyun; Yin, Zongzhi; Akinwunmi, Babatunde; Ming, Wai‐kit (Psychiatric research and clinical practice, 2021)
Objective The novel coronavirus disease (COVID‐19) outbreak has aroused a range of negative effects. Such considerable influence can be greater in vulnerable populations including pregnant women. This study aimed to assess the presence of prenatal depression (PND, as an important risk factor of postpartum depression) and post‐traumatic stress disorder (PTSD) and to characterize infection‐induced preventive behaviors and psychological responses in the early phase of COVID‐19 outbreak. Methods Based on a population‐based sample of pregnant women from all regions in China, presence of probable PND and suspected PTSD were assessed using the Edinburgh Postnatal Depression Scale (≥13) and the PTSD Checklist (≥14), respectively. A web‐based questionnaire was used to assess psychological and behavioral responses to COVID‐19. Results Among a total of 1908 questionnaires returned, 1901 women provided valid data (mean [SD] age, 28.9 [4.7] years). High prevalence of probable PND (34%) and suspected PTSD (40%) among pregnant women was observed. Those with suspected PTSD presented six times higher risk of probable PND than the non‐suspected (OR=7.83, 95% CI: 6.29–9.75; p<0.001). Most women (91%–96%) reported anxiousness about infection of themselves and the members within their social network. Lack of security and loss of freedom were reported in approximately two‐thirds of pregnant women. More frequent preventive behaviors, including handwashing, use of facemasks, and staying at home, were undertaken in more than 80% of the sample. Anxiousness of miscarriage and preterm birth were prevalent (>75%). Conclusions High prevalence of PND and PTSD and high levels of anxiety suggest profound impacts of the present outbreak on mental health. This calls for special attention and support for vulnerable populations. Mental health care should become part of public health measures during the present outbreak and should continue to be intensified to empower the health system for post‐outbreak periods. Highlights High prevalence of probable prenatal depression (PND) and suspected post‐traumatic stress disorder was observed during the early stage of COVID‐19 pandemic, and those with suspected post‐traumatic stress disorder presented six times higher risk of probable PND than the non‐suspected Higher levels of psychobehavioral responses were reported by pregnant women Our findings call for special attention and support for vulnerable populations